The lost dinosaurs the astonishing discovery of the world's largest prehistoric nesting ground - Chiappe, Luis M.; Dingus, Lowell (London Abacus, an imprint of Time Warner Books UK, 2002)
"Walking on Eggs is the inside story behind one of the most significant paleontological discoveries in history. In November 1997, Luis M. Chiappe and Lowell Dingus led an elite team of paleontologists and geologists into the rugged and desolate badlands of Argentina. Unsure of what they would find, Chiappe and Dingus knew that this region had produced many spectacular specimens of dinosaurs and fossil birds over the last century. Nothing could have prepared them, however, for the headline-grabbing discovery they were about to make: a massive dinosaur nesting ground covering more than a square mile and littered with tens of thousands of large, unhatched dinosaur eggs. Containing the first fossils of embryonic dinosaur skin ever found, the eggs gave rise to a host of mysteries. What species laid the eggs, and when? How were they preserved? And most intriguingly, what ancient catastrophe - deeply rooted more than 70 million years in the past - prevented them from hatching?"
Introduction: The moment of discovery -- 1. Patagonia: a faraway land full of fossils -- 2. What were we searching for and how did we decide where to look? -- 3. The scene of an ancient catastrophe: Auca Mahuevo -- 4. Compiling a list of possible victims: a brief history of dinosaurs -- 5. Dinosaur eggs: evolutionary time capsules -- 6. Finding evidence in the eggs at our forensic labs: dinosaur embryos and embryonic skin--the rarest of all dinosaur fossils -- 7. Establishing the time of death: evidence from clocks in the rocks -- 8. Establishing the cause of death: uncovering clues in the rocks -- 9. Our fifteen minutes of fame: is Auca Mahuevo the real Jurassic Park? -- 10. Our return to the scene of the catastrophe: the 1999 expedition -- 11. Was the nesting site used more than once? discovering new egg layers -- 12. Were giant dinosaurs gregarious? our nests of eggs and other evidence -- 13. An awesome predator: discovering a skeleton of the sauropods' adversary -- 14. The Y2K expedition.
"An Abacus book."
Includes bibliographical references (page 205) and index.
Keywords: Chiappe, Luis M; Dingus, Lowell; Dinosaurs -- Eggs -- Argentina -- Neuquén (Province); Fossils -- Argentina -- Neuquén (Province)